1997
DOI: 10.1016/s1074-7613(00)80395-7
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Editing in a Transgenic Mouse Model: Site, Efficiency, and Role in B Cell Tolerance and Antibody Diversification

Abstract: Mice carrying transgenic rearranged V region genes in their IgH and Igkappa loci to encode an autoreactive specificity direct the emerging autoreactive progenitors into a pre-B cell compartment, in which their receptors are edited by secondary Vkappa-Jkappa rearrangements and RS recombination. Editing is an efficient process, because the mutant mice generate normal numbers of B cells. In a similar nonautoreactive transgenic strain, neither a pre-B cell compartment nor receptor editing was seen. Thus, the pre-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
280
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 265 publications
(300 citation statements)
references
References 61 publications
18
280
2
Order By: Relevance
“…B cell negative selection induces a wide range of responses. Some negatively selected B cells, such as anti-dsDNA and anti-MHC class I B cells, undergo receptor editing as a means of altering their specificity or are deleted in the bone marrow (5,40). Other autoreactive B cells that developmentally arrest in the spleen have lower than normal surface IgM levels (30,41) and in some cases elevated levels of activation markers such as CD44, HSA, and MHC class II, indicating that they have encountered Ag (30).…”
Section: Discussionmentioning
confidence: 99%
“…B cell negative selection induces a wide range of responses. Some negatively selected B cells, such as anti-dsDNA and anti-MHC class I B cells, undergo receptor editing as a means of altering their specificity or are deleted in the bone marrow (5,40). Other autoreactive B cells that developmentally arrest in the spleen have lower than normal surface IgM levels (30,41) and in some cases elevated levels of activation markers such as CD44, HSA, and MHC class II, indicating that they have encountered Ag (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that while an autoreactive BCR will induce L chain gene rearrangement, a nonautoreactive BCR will not (31). Although editing in ⌬V mice cannot be manifested by a change in L chain, because ⌬V receptors do not contain L chains, it is possible to evaluate the nature and the extent of L chain gene rearrangement by semiquantitative methods (24).…”
Section: Evidence For Secondary L Chain Gene Rearrangement In ⌬V Cellsmentioning
confidence: 99%
“…However, the expression of a functional BCR does not always terminate light chain gene rearrangement (6). One well-documented situation in which rearrangement continues is when the Ag receptors on the newly formed immature B cells possess autoreactive specificity (7)(8)(9). This secondary V(D)J rearrangement, referred to as receptor editing, occurs in IgM ϩ , IgD Ϫ immature B cells in the bone marrow (10,11).…”
mentioning
confidence: 99%